Analisis Penerapan Projek Penguatan Profil Pelajar Pancasila (P5) dalam Pembentukan Karakter Pelajar Pancasila pada Siswa SMPN 6 Kota Solok - Rahmawati, Lisa; Basyirun, Fajri; Ikhwan, Ikhwan (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This research is motivated by the need for student character development according to the Pancasila Student Profile at SMPN 6 Solok City through the Pancasila Student Profile Strengthening Project (P5), where initial observations show a decline in positive character such as lateness and lack of student enthusiasm, so that an analysis of its application is needed to foster the values ​​of faith, noble morals, global diversity, mutual cooperation, independence, creativity, and critical reasoning. The purpose of this study was to analyze the implementation of the Pancasila Student Profile Strengthening Project (P5) in the character building of Pancasila students in SMPN 6 Solok City. The study involved key informants including students, teachers, curriculum representatives and P5 coordinators, as well as additional informants such as parents, school committees, and administrative staff. The analysis followed the interactive model of Miles and Huberman, encompassing four main steps: data collection (observation, interviews, documentation), data reduction (summarizing and focusing on themes), data presentation (narrative/text), and drawing conclusions/verification. In this study, the results showed that the implementation of P5 had a positive effect on the formation of student character, marked by increased spiritual awareness, politeness, cooperation, creativity and critical thinking, although challenges in discipline and cleanliness still remained. In this study, suggestions included strengthening synergy between schools, teachers, parents and ongoing support for the optimization of P5.